An Assessment of Malaysia’s Compliance with the Current and Future International Standards of Criminal Enforcement Measures to Protect against Copyright Piracy on a Commercial Scale - Adam, Ainee (Journal of Malaysian and Comparative Law, 2016)
Being a WTO member, Malaysia is compelled to implement the standard of criminal enforcement measures established in Article 61 of the Trade-Related Aspects of Intellectual Property Rights Agreement in its national copyright laws. More specifically, Malaysia is required to criminalise wilful copyright piracy on a commercial scale and make available imprisonment and/or pecuniary penalties as punishment for the offence. The punishment should be set at a level sufficient to provide a deterrent, consistent with that made available for crimes of a corresponding gravity. While the Trade-Related Aspects of Intellectual Property Rights Council confirmed Malaysia’s compliance with the standard in 2003, it is time for the penal provisions in the Copyright Act 1987 (Malaysia) to be re-assessed particularly in view of Malaysia’s keen interest in ratifying the Trans-Pacific Partnership Trade Agreement (TPPA), and by extension, subscribing to a higher standard of criminal enforcement measures against copyright piracy on a commercial scale. The article first examines the penal provisions in the Copyright Act 1987 (Malaysia) with reference to the article 61 standard and subsequently assesses if the TPPA standard will herald a change in the national enforcement regime.